European public health policy - a common agenda to strengthen the social pillar of the EU - Hammermeister, Julia; Kočí, Kateřina; Machoň, Miloslav, 1988-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The European Union's policy competences are divided into three different categories: exclusive, shared and supporting. The European Union has merely shared competences in regard to health policy - still it manages to affect change. This paper will examine the extent of the European health policy in regards to strengthening the European social policy.
Vedoucí práce: Kateřina Kočí
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses